1976
DOI: 10.1002/bjs.1800630625
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgical haemorrhoidectomy

Abstract: One hundred consecutive cases of haemorrhoids were treated by cryosurgery. The cryoprobe used is a convenient and simple instrument and gave a satisfactory result in 94 of the patients. The technique and complications are described. The patients were treated as outpatients, usually without anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This problem was also reported by O'Connor [29]. Wilson and Schofield [30] and Savin [31] also reported an increased incidence of serous discharge and prolonged recovery for such patients. Smith et al [32] reported a study in which both closed hemorrhoidectomy and cryotherapy were performed in 26 patients.…”
Section: Discussionsupporting
confidence: 63%
“…This problem was also reported by O'Connor [29]. Wilson and Schofield [30] and Savin [31] also reported an increased incidence of serous discharge and prolonged recovery for such patients. Smith et al [32] reported a study in which both closed hemorrhoidectomy and cryotherapy were performed in 26 patients.…”
Section: Discussionsupporting
confidence: 63%
“…Many authors 1–4 have reported that relief of hemorrhoidal symptoms can be achieved by nonsurgical procedures such as sclerotherapy, ligation with a rubber band, and cryotherapy 5,6 and that surgical treatment is necessary in only a few such cases. Our own e−perience leads us to believe that cryosurgery gives the best results of all these procedures, provided that it is performed by a suitably qualified surgeon 7,8 who is aware of the inherent limitations of the cryogen and of the instrument used, and is thoroughly familiar with the anatomy and pathology of internal and e−ternal hemorrhoids.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of cryotherapy is that destroying local nerve endings 1 enables avoidance of the pain, inconvenience and disability associated with classic surgical hemorrhoidectomy. Nine of our patients who had previously undergone surgical hemorrhoidectomy described cryotherapy as “miraculous” in comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Jaundice has been reported due to injection directly into the inferior hemorrhoidal veins [112]. Jaundice has been reported due to injection directly into the inferior hemorrhoidal veins [112].…”
Section: Submucosal Sclerosis According To Bensaudementioning
confidence: 99%
“…Local anesthesia may be required; sedation or prescription of analgesic is necessary. Successes range from 45% to 88% of patients treated [16,35,85,112]. This requires the patient to wear anal pads for 2-3 weeks.…”
Section: Hemorrhoids 63mentioning
confidence: 99%